Low-Density Lipoprotein Contributes to Endometrial Carcinoma Cell Proliferation, Migration, and Invasion by Activating the JAK–STAT Signaling Pathway - Lifan Shen; Chen Zhang; Kaiying Cui; Xin Liang; Genhai Zhu (Analytical Cellular Pathology)
Background. Cholesterol-rich low-density lipoprotein (LDL) particles have been demonstrated to regulate breast cancer cell proliferation and migration, but their biological function and relevant mechanisms in endometrial carcinoma (EC) remain unclear Methods. Serum and tissue samples were collected from EC patients (n = 50) and patients with benign endometrial hyperplasia (n = 50). Ishikawa and RL95-2 cells were stimulated with different concentrations of LDL, followed by treatment with a JAK2 inhibitor (SD-1029). LDL concentrations were determined by ELISA. The in vitro biological behavior of cells was examined using the CCK-8 assay, EdU staining, and Transwell assay. The tumorigenicity of LDL in vivo was examined using a xenograft mouse model. western blotting, immunofluorescence, and immunohistochemistry studies were performed to measure related protein expression. Results. The LDL concentrations and levels of p-JAK2 and p-STAT3 expression were elevated in the clinical samples. Similar trends in expression were detected in EC cells after LDL stimulation. LDL treatment significantly promoted EC cell proliferation, migration, and invasion, and also upregulated p-JAK2 and p-STAT3 expression in a dose-dependent manner. Moreover, SD-1029 dramatically blocked the LDL-mediated effects on EC cells. Intravenous injection of LDLs promoted tumor growth in the xenograft nude mice, and also increased p-JAK2, p-STAT3, and Ki-67 expression, and downregulated caspase-3 expression. Conclusions. These findings indicate that LDLs exert an oncogenic effect in EC cells by activating the JAK/STAT signaling pathway, and also suggest the JAK/STAT pathway as a possible therapeutic target for EC.